Do we need to do overcorrection in Blount’s disease? - Eamsobhana, Perajit (Springer Berlin Heidelberg, 2014)
PURPOSE: In order to prevent recurrent deformity, overcorrection in Blount’s disease has been a common practice by most paediatric orthopaedic surgeons. However, some patients have persistent valgus alignment resulting in awkward deformity. The femoro-tibial angle (FTA) was measured in this series of cases to determine the necessity of such practice. METHOD: During 1998–2010, patients with Blount’s disease stage 2 by Langenskiold, aged from 30 to 40 months who had failed from bracing and underwent valgus osteotomy were included. Seventeen legs had postoperative FTA 7–13° (group 1) and 48 legs had postoperative FTA more than 13° (group 2). ROC curve was used to determine the appropriate FTA that was suitable to prevent recurrence. RESULTS: Four legs had recurrence (28.6 %) in group 1 and six legs (12.5 %) had recurrence in group 2. Chi-square test between two groups were not statistically significant in recurrence (p = 0.434). Age and BMI were not statistically significant between recurrent and non-recurrent groups. The ROC curve shows that overcorrection more than 15° did not show benefit to prevent the recurrence in Blount’s stage 2. CONCLUSION: Our study showed that the overcorrection group had non-statistically significant recurrence compared to the non-overcorrection group, and overcorrection more than valgus 15° has no benefit to prevent recurrence.